An Analysis of Figurative Language on Digital Children’s Poems with Friendship Theme Available at Weareteacher.Com Website - Firdelina, Shabira; Marlina, Leni (Universitas Negeri Padang, 2024)
This research examines figurative language in digital children's poems onWeareteacher.com, highlighting how metaphors, similes, and personification createrelatable imagery that captivates young readers while fostering cognitive andlinguistic growth. A qualitative methodology is employed to analyze a selectedarray of diverse digital poems targeting young audiences, utilizing a codingframework to methodically identify and categorize figurative language instances.Data collection entails downloading and compiling poems for in-depth textualanalysis, concentrating on the contribution of figurative elements to meaning,emotional resonance, and overall attractiveness. In addition, the examination looksinto the educational relevance of these texts for English learners, whether they areyoung or adult, particularly for those pursuing English as a Foreign Language(EFL), underlining how the complexity of figurative language supports languagedevelopment and enhances the educational experience. The purpose of thisinvestigation is to present important observations regarding the function offigurative language in children's poem and its prospective applications in teaching.